Análise ambiental da Bacia do Ribeirão Fazenda Velha, Ibiúna-SP: subsídios para o planejamento ambiental e conservação dos recursos hídricos - Lorca Neto, Rafael Ocanha (Universidade Federal de São Carlos, 2013)
This study aimed to conduct an environmental analysis of the River Fazenda Velha Watershed, providing subsidies to planning for the conservation of water resources. We used a set of tools in a Geographic Information System - GIS for spatial interpretation of data, statistical analysis and preparation of cartographic products. The maps generated were used to characterize the physical area and its environmental analysis. In the field trips were identified many environmental problems such as siltation of water bodies, soil erosion, release of untreated effluents and deforestation of riparian vegetation. After the environmental analysis was prepared a map of priority areas for conservation of water resources. The sector of the upper basin is the region that contains most of the priority areas and very extremely high. Due to the structuring of relief, marked by the presence of interfluves, with steep slopes (above 20%) becomes a strategic area for groundwater recharge and protection of soil and springs. Were also identified priority areas in the field of middle basin, characterized by slopes greater than 20% and the presence of natural vegetation. With the map of priority areas was possible to draw a map of Environmental Zoning, taking into account the conservation of water resources and the use for human activities. The proposed zoning map has four zones: Zone Conservation of Water Resources, Sustainable Use Zone, Intensive Use Zone, Agricultural Use Zone.
Environmental analysis in the River Fazenda Velha Watershed, Ibiúna-SP. Subsidies for water conservation.
Keywords: bacias hidrográficas; abastecimento de água; planejamento urbano; zoneamento ambiental; recursos hídricos; environmental zoning, watershed, water resources; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS